OPTIMALISASI MODEL EFISIENSI ENERGI DAN BIAYA TERHADAP TINGKAT PENDAPATAN DENGAN CLUSTERISASI NELAYAN TANGKAP DI PROVINSI JAMBI - Tona Aurora Lubis; Zulkifli Zulkifli; Muhammad Safri (Jurnal Sains Sosio Humaniora, 2017)
This research is important and interesting, especially for Jambi province since studies first year will be able to classify the fishermen catch with the system clusterisasi, able to identify and analyze the impact of energy efficiency and cost to the level of income of fishermen fishing, formulate a model of the development of energy efficiency and cost against income level with clusterisasi fishermen catch, as well as the first study of formulating a development model of energy efficiency and cost to the level of income by fishermen catch clusterisasi This study uses a combination of research methods (mixed method), which is a combination of qualitative and quantitative research methods. The type of research used is a combination of Exploratory Sequential Design, which is in the early stages of research using qualitative methods and the next phase using quantitative methods. The conclusion of this study is clusterisasi fishermen in Jambi Province can be classified into three categories: full of fishermen, and fishermen main sideline, as well as additional odd fisherman. The impact of energy efficiency and cost to the level of fishing income generating variable Energy Efficiency and Cost (EEB) to four (4) indicators reflective namely: the type of vessel (JK), speed boat (KK), operation of a ship (OK), the pattern of arrests (PP) and variable Fishermen performance Capture (KNT) with (a) a reflective indicator is the level of income (TP). A model of energy efficiency and cost against pendatan with clusterisasi fishermen fishing in the province of Jambi is that energy efficiency and cost (EEB) which is reflected by speed boat (KK) and ship operations (OK) has a significant influence on the performance of the fishermen catch (KNT) reflected income level (TP). This study is important and interesting in order to get funding for this research study second year (2017), so it can answer Fator factors internal and external that affect the welfare of fishermen fishing in the province of Jambi.